Patient perspectives on pulmonary hypertension in the United States: Burdens, expectations, and goals - Kirsten Braley; Kathleen Richardson; Lenise Whitley; Katie Werner; Linda Appleby (Pulmonary Circulation, 2023)
Abstract Pulmonary hypertension (PH) is a life‐threatening, debilitating disease caused by increased blood pressure in the pulmonary arteries. As patients living in the United States, we have unique insights into the journey from diagnosis and treatment within the US healthcare system and the significant impact that PH has on our quality of life. While there have recently been advances in PH management, there are several areas of PH care which we feel should be reassessed and improved. Commonly, diagnosis is lengthy and convoluted due to the rarity of the disease and limited knowledge of PH in primary care. There are also barriers to obtaining the right treatment and we feel that a more holistic approach to care is needed. Mental health is commonly overlooked and should be an integral part of patient care, as should elements such as nutritional advice, cardiopulmonary rehabilitation, and sexual health. PH patient associations play a key role in providing social, educational, and financial support to patients and caregivers alongside PH research and advocacy. As patients, we feel that we need to advocate for correct diagnosis, timely referral, and optimal treatment, in addition to overcoming the financial and/or administrative hurdles to obtain these. We propose several future goals to help empower patients to play an active, central role in their care and to improve all aspects of PH management. We advocate for further use of the patient voice in research and clinical development programs, including the use of patient‐reported outcomes that have been developed with patient input.